Small-scale fisherfolk in Papua New Guinea: Perspectives on climate variability and its impact on coastal fishing operations and activities - Louis George Korowi; Mubarak Mammel; Baker Matovu; Pei-Ting Huang; Ajith Raj; Yao-Jen Hsiao; Ming-An Lee (Environmental Challenges, 2025)
This study aimed at exploring climate variability and small-scale fishers’ perspectives on how climate variability impacts fishing operations in East New Britain (ENB) province in Papua New Guinea. Climate data from 2000 to 2020 and participatory interactions with 80 fishers in three fishing villages of ENB were utilized and conducted. Findings revealed that traditionally, small-scale fisheries (SSF) of ENB have sustained the livelihoods of coastal and island communities for millennia. However, the projected impacts of climate change (CC) are posing significant challenges to fishers, yet limited research has explored the plight of SSF, and fishers, including their knowledge of CC variability. Coastal livelihoods and activities are dependent on fishing and fishing knowledge that is cross-generational. Women and renowned fishers (with unique fish harvesting skills) are critical actors, e.g., in identifying historically rich fishing grounds, and helping fishers or local communities in fishing activities and community festivals, e.g., conventional marriages. Fishing is a sociocultural identity, and this has led to emphasis on sustainable fishing practices by fishers and some key stakeholders, e.g., on the utilization of eco-friendly gear, wooden fences, marking of fish migratory routes, and stone traps. However, the fishers population is ageing. During peak fishing seasons that last one week per month, and depending on the fishing method, fishers earn between 300 and 1500 Kina (72–359 USD) daily. Increasing socioecological shifts were reported, including reducing fish economic value, changing fishing locations, and declining catch. Since 2000, sea surface temperatures (SSTs) have increased by about 1 °C and in December 2020, SST reached 30.20 °C, with the northern and eastern coastal zones of PNG being greatly affected. Fishers reported four critical concerns that affect their livelihoods and which could increase their vulnerability to human-environmental risks. 65 % of fishers are uncertain or have limited knowledge on CC, climate variability, its drivers, and associated impacts. Fishers emphasized fourteen perspectives that could mitigate the increasing socioecological shocks and vulnerabilities they face. Most of the perspectives cut across socio-cultural, economic, institutional, and environmental domains of sustainable fishing practices. Five starting points for sustainability transformations for policy and research are recommended including: (1) education programs on ecological processes, fishers’ local socioecological knowledge and climate variability, (2) collaborative stakeholder engagements in CC-policy design and community adaptation and mitigation actions, (3) integrated socio-ecological approaches on marine resource management, cost-benefit sharing, and co-management, (4) capacity-building programs and initiatives, and (5) proactive national-level prioritization of coastal and island fishers’ rights. Although fishers in ENB are reportedly uncertain about CC knowledge, and yet there is evidence of pronounced climate variability, ocean environmental parameters, threatened fisheries and livelihood vulnerabilities, collaborative and effective fisheries management approaches might mitigate it. This can be via proactive integration of CC adaptation, sustainable fisheries management, better governance within the existing institutional structures, and support for community-led resilience strategies.